Planning the required nursing personnel to respond to care needs - Gaviria Noreña, Dora Lucia (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> An approach is undertaken of the concepts and methodologies concerning the planning of the nursing personnel required to respond to the care needs of individuals, families, and groups. Planning is evermore founded on the nature of caring for human beings within the context of life, which endows the existence of the person-patient with sense and significance, as well as the nursing personnel, according to the culture and the social setting in which it is developed. Knowing what and how much personnel is required to offer caregiving has been marked by the calculation of coefficients and time averages to execute activities, the description of the work load that includes studying times and movements, analysis of supply and demand of human resource, mediated by the profession’s regulations in each country and by inquiry within the context of caregiving. However, consensus has not been reached with respect to this process, but it is concluded that it is a policy action that requires regulation, investigation, and group work by nursing to make caregiving visible and legitimate as a public service that maintains life and health and which also favors and mitigates processes of disease and death faced by human beings. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->